Seismic Analysis on the Behaviors of Meru Structures: A Sacred Building in Balinese Temples - I Ketut Sudarsana; Gede Adi Susila; Ni Putu Silvi; Ngakan Ketut Acwin Dwijendra (Modelling and Simulation in Engineering)
Seismic behaviors of the Meru structure as one of the sacred buildings in Balinese Temples have not been investigated extensively. Most research investigated the Meru building in terms of its philosophy and history. The Meru buildings were observed to survive many earthquake events that occurred in Bali Islands. This paper presents the analysis results of the Meru structure in responding to earthquake excitations. As many as five types of the Meru structure traditionally built were modeled and analyzed using finite element-based software. Each type of Meru has three variations in the roof masses that were obtained from increasing the roof thickness from 500 mm, 600 mm, and 700 mm. Time history analysis follows Newmark’s average acceleration method with an input earthquake record of the scaled El-Centro N-S 1940 to meet seismic conditions in the Bali area. The results show that the dynamic responses of the Meru structure increase as the number of roof levels and mass increase. All of the Meru types have met the limitation of the code’s lateral allowable limits. The dimensions of the structural elements determined according to Balinese scripts can provide capacity greater than twice the capacity demand. Keeping the roof mass in a certain proportion with the mass of the lowest roof twice of the above one will keep the Meru stable during an earthquake.